INVESTIGATION OF BEHAVIORAL CHANGES IN INDIVIDUALS’ DURING THE COVID-19 PANDEMIC PERIOD (Third Sector Social Economic Review, 2021)
COVID-19 is a deadly virus that spreads rapidly from China to the world. The COVID-19 outbreak has deeply affected individuals physically, socially and psychologically. In this study, it was aimed to examine the effect of individuals' ability to organize personal presentation on perceived stress, insufficient self-efficacy and perception of stress / discomfort during the COVID-19 pandemic. The data were obtained from 443 volunteers between the ages of 18-65 living in Konya, accessible through an online questionnaire and agreeing to participate in the study. As a result of the analyzes, it was determined that the high ability to organize personal presentation has an effect that reduces perceived general stress, insufficient self-efficacy and stress / discomfort perception. As a result, it has been found that those who adapt to the changes that occurred during the COVID-19 pandemic period are less stressed. It is important to increase individual efforts to adapt to the conditions required by the pandemic period in order to control the pandemic and to minimize individual stress.
Keywords: COVID-19; self-monitoring; stress; Konya